Coordinating EU foreign policy on China : a comparative analysis of two member states' bilateral relations with China - Březinová, Klára (2023)
This thesis investigates the coordination and coherence of German and Czech foreign policies within the European Union's Common Foreign and Security Policy (CFSP), particularly towards China. The study is grounded in theories of liberalism and liberal intergovernmentalism. It examines the integration of member states' interests into the CFSP, focusing on Germany and Czechia's approaches towards China during the EU Commission's term from December 2019 to July 2023. The research analyzes national strategies, heads of government speeches, and EU strategy documents. It first compares member states' policies horizontally and then with the EU's stance. While Germany adopts a nuanced approach, labelling China as a partner, competitor, and systemic rival with a growing focus on the rivalry aspect in the later years, Czechia's policy is less pronounced, more cautious and security-focused. The thesis observes a shift in both countries' foreign policies post-Ukraine war, emphasizing resilience and reducing dependency in critical domains. Surprisingly, the EU's policy aligns more closely with the German approach, raising questions about the influence of member states on the EU's foreign policy. The study contributes to understanding European integration and the dynamics between member states and the EU in foreign policy coordination.